2004
DOI: 10.1007/s00421-004-1090-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic implications of resistive force selection for oxidative stress and markers of muscle damage during 30�s of high-intensity exercise

Abstract: The purpose of this study was to compare power outputs, and blood concentrations of lipid hydroperoxides (LH), malondialdehyde (MDA), creatine kinase (CK), myoglobin (Mb) and lactate ([La-]B) following 30 s of maximal cycle ergometry when resistive forces were derived from total-body mass (TBM) or fat-free mass (FFM). Alpha-tocopherol (AT), retinol (R) and uric acid (UA) concentrations were also measured to qualify the activity of antioxidants. Cardiac troponin levels were determined to exclude myocardial dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 29 publications
7
70
2
3
Order By: Relevance
“…Changes in UA concentration in the blood have been used in previous studies as an indicator of oxidative stress occurring after anaerobic exercise [3,6,[16][17][18][19]. The results of the previous studies are not conclusive because UA is a product of purine metabolism and, at the same time, non-enzymatic antioxidant that affects the total antioxidant capacity of the blood [20].…”
Section: Introductioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Changes in UA concentration in the blood have been used in previous studies as an indicator of oxidative stress occurring after anaerobic exercise [3,6,[16][17][18][19]. The results of the previous studies are not conclusive because UA is a product of purine metabolism and, at the same time, non-enzymatic antioxidant that affects the total antioxidant capacity of the blood [20].…”
Section: Introductioncontrasting
confidence: 41%
“…A significant increase in the blood concentration of UA beginning at various times after the completion of anaerobic exercise could be found (3, 10, 15, 60 minutes) [3,16,18,19]. Peak concentration of UA in the blood occurred 1 hour after the end of anaerobic exercise, with a subsequent decrease in concentration up to 24 hours [3], or the UA concentration decreased immediately after exercise and increased after 24 hours of rest [17]. In other studies, no significant changes in UA concentration in the blood 24 hours after anaerobic exercise were found [6].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In fact, many studies have reported that an acute exhaustive maximal exercise task lasting only 30s (i.e. the Wingate test) is capable of inducing systemic changes in redox homeostasis (Groussard et al, 2003a;Groussard et al, 2003b;Baker et al, 2004;Cuevas et al, 2005;Cooke et al, 2008;Bloomer and Smith, 2009;Arent et al, 2010). For example, Groussard et al (Groussard et al, 2003b), employing electron paramagnetic resonance (EPR) spectroscopy, reported a twofold increase in lipid-derived radicals in plasma after 30s of cycling.…”
Section: Effects Of Very Short Duration Exercise On Redox Homeostasismentioning
confidence: 99%
“…Overproduction of ROS (arising either from mitochondrial electrontransport chain or excessive stimulation of NAD(P)H) results in oxidative stress (Marian et al, 2007), a deleterious process that has been implicated in various pathological conditions involving cardiovascular disease, cancer, neurological disorders, diabetes, ischemia/reperfusion, other diseases and ageing (Baker et al, 2004;Valko et al, 2007;Stadtman, 2004;Dalle-Donne et al, 2005;Gupte & Mumper, 2009;Khandrika et al, 2009). Free radicals react with lipid and cause peroxidative changes that result in enhanced lipid peroxidation (Zwart et al, 1999;Girotti, 1985).…”
Section: Discussionmentioning
confidence: 99%